Teacher professional learning through lesson study: teachers' reflections. Issue 4 (28th August 2020) - Fox, Alison; Poultney, Val
Abstract : Purpose: This study examines the experiences of five teachers working in two English secondary school subject departments after being given the opportunity to engage with Lesson Study (LS) to increase student performance in their subject areas. This study aimed to reveal the drivers for the teachers' engagement in LS, and how this experience of Joint Professional Development (JPD) might be contributing to their learning as teachers. Design/methodology/approach: This study applies an analytic approach to evidencing teacher learning, based on the work of Knud Illeris, offering this as a methodological contribution to the field of professional development literature. Findings: Findings reveal that, despite all the teachers developing a passion for learning through LS, there are constraints on its sustainability and impact which can be attributed to the teachers' broader contexts and which affected them differently. The constraints centre on tensions between priorities and agendas within and beyond the school, related largely to budgets and visions of staff development. Research limitations/implications: This focused study on two subject departments engaging in LS limits its generalisability in terms of findings. However, the study offers a practical research application of a model of learning for analysis of teacher reflections on collaborative learning experiences. Originality/value: Understanding individual teacher reflections on LS experiences is under-represented in the literature, in particular studies providing insights into conditions conducive and constraining to JPD.